Role of aspirin dose in reducing uterine artery resistance in 16-24 weeks pregnant women with abnormal uterine artery resistance - Muhammad Arief Adibrata; Agus Sulistyono; Ernawati Ernawati (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To compare the decrease of resistance index (RI) from uterine artery in pregnant woman receiving low dose aspirin therapy between 80 mg/day and 125 mg/day who had abnormal doppler velocimetry (DV) ultrasound examination at 16-24 weeks.Materials and Methods: An experimental study using double blind randomized clinical trial design. Subjects were from Mulyorejo and Kalijudan public health service in Surabaya, that included pregnant women with 16-24 weeks of pregnancy with abnormal uterine artery velocimetry ultrasound. The results of ultrasound Doppler examination were divided into four levels; normal (RI<0.58; (-) diastolic notching), level I (RI> 0.58; (-) diastolic notching), level II (RI<0.58; (+) disatolic notching) and level III (RI> 0.58; (+) diastolic notching). Uterine doppler ultrasound examination was performed at Fetomaternal Division, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Airlangga, Dr. Soetomo Hospital, Surabaya, Indonesia, by fetomaternal consultants before and after the admin-istration of low-dose aspirin of 125 mg/day and 80 mg/day for four weeks.Results: Ninety subjects were obtained and randomized into 2 groups, with 45 subject in each group. Before treatment, in 125 mg/day group those with level I were 34 subjects and level III 11 subjects. In 80 mg/day group, level I 41 subjects, level II 2 subjects and level III 2 subjects. After 4 weeks of treatment, a second DV USG was performed in Aspirin 125 mg/day group. Normal were 40 subjects, level I 4 subjects, and level III 1 subject. In aspirin group 80 mg/day, normal 22 subjects, level I 19 subjects and level III 4 subjects. The analysis was performed with Wilcoxon test before and after treatment in both aspirin treatment group 125 mg/day and 80 mg/day with p value respectively, p=0.001 and p=0.005.Conclusion: Compared with aspirin of 80 mg/day, aspirin of 125 mg/day is more superior to decrease uterine arterial resistance in pregnant women with ultrasound uterine arterial doppler velocimetry at 16-24 weeks gestational age.